Essential Programs and Services: The Basis for a New Approach for Funding Maine’s Public Schools - Silvernail, David; Bonney, Weston (Maine Policy Review, 2001)
In this article, David Silvernail and Weston Bonney extend Maine Policy Review’s coverage of school funding reform by introducing a new approach called Essential Programs and Services (EPS). Traditional approaches to school funding evaluate education in terms of revenue—by taking whatever dollars are available and dividing them in such a way as to ensure there are equal education dollars behind each child. In contrast, the Essential Programs and Services model focuses first on student outcomes, and second, on the services and resources needed to achieve these outcomes. The EPS model then defines what is adequate in terms of resources and dollars to get the job done. The authors propose that adoption of such an approach may finally put to rest Maine’s perennial arguments over what is a ‘sufficient’ funding level for the state’s schools. More importantly, it may ensure that all Maine students have equitable opportunities to achieve the American dream.